Typical presentation of mucopolysaccharidosis type IVA: a case report - Ashrita, Kovvuru; Lokesh, Ethuri (International Journal of Contemporary Pediatrics, 2024)
Mucopolysaccharidosis (MPS) IVA, or Morquio syndrome, is a rare lysosomal storage disorder characterized by skeletal dysplasia. It is caused due to deficiency in the enzyme N-acetylgalactosamine-6-sulfatase (GALNS), which results from an autosomal recessive mutation in the GALNS gene. The frequency of this mutation is equivalent in men and women. Here in, we present the case of Morquio syndrome, in a male child of twin gestation with poor antenatal and natal history. The peculiar presentations are those of skeletal deformities, coarse facial features, recurrent respiratory tract infections, and a history of NICU admission for meconium aspiration syndrome. This case is unique because, despite a negative family and prenatal history, and one of the twins being unaffected which adds to its appeal. Later, on biochemical and radiological investigations, he was diagnosed with mucopolysaccharidoses IVA and ultimately managed him supportively.